Correction: Di Febo (2025). Transition Risk in Climate Change: A Literature Review. Risks 13: 66 - Elisa Di Febo (Risks, 2025)
As requested by the Editorial Office, the authors have removed Eliana Angelini from the author list due to insufficient contribution to the published paper (Di Febo 2025) [...]